Association between parent mental health and paediatric TBI: epidemiological observations from the 1987 Finnish Birth Cohort. Issue 4 (23rd January 2018) - Lowery Wilson, Michael; Tenovuo, Olli; Gissler, Mika; Saarijärvi, Simo
Abstract : Background: This study examined whether parental mental illness has implications for child risk for traumatic brain injuries (TBI). Method: Data on 60 069 Finnish children born in 1987 and their parents were examined for demographic and mental health-related variables in relationship with paediatric TBI. Altogether, 15 variables were derived from the cohort data with ICD-10 F-codes being available for mental health diagnoses for all parents. Bivariate and multivariate analyses were carried out using inpatient and outpatient diagnoses of child TBI. Results: Paternal disorders due to psychoactive substance use (F10–F19) was associated with an increased inpatient TBI (OR=1.51; CI=1.07 to 2.14). Mood disorders (F30–F39) were associated with higher rates of outpatient TBI (OR=1.42; CI=1.06 to 1.90). Paternal personality and behavioural disorders (F60–F69) were linked with a twofold increase in risk across both categories of child TBI (OR=2.35; CI=1.41 to 3.90) and (OR=2.29; CI=1.45 to 3.61), respectively. Among the maternal mental health factors associated with child TBI, schizophrenia and other non-mood psychotic disorders (F20–F29) were associated with an increase in inpatient traumatic brain injuries (iTBI) (OR=1.78; 1.22 to 2.59). Mothers having mood disorders (F30–F39) were more likely to have had a child who experienced an iTBI (OR=1.64; CI=1.20 to 2.22). Mothers with personality and behavioural disorders (F60–F69) were also found to have had children with an increased risk for iTBI (OR=2.30; CI=1.14 to 3.65). Conclusion: Taken together, these data should call attention to methods and strategies designed to augment and support caregiving environments with modalities that can foster mutually supportive households in cooperation with parents who have been diagnosed with a mental disorder.